Is there such a thing as a capitalist eschatology?. (February 2022) - Palmås, Karl; Ekberg, Kristoffer; Åberg, Anna
Highlights: Contemporary entrepreneurs' projections for multiplanetary life constitute a productive object of study. As end-of-the-world narratives, such projections can be understood as eschatological accounts. These accounts, in turn, may influence of business leaders, financiers and engineers, as well as broader publics. This "capitalist eschatology" can be studied in relation to immediacy and inevitability, as well as investment and ideology . Abstract: This short communication presents preliminary notes about how to study the role of eschatology in the contemporary economy, focusing specifically on space-colonizing ambitions of US entrepreneurs such as Elon Musk. It is suggested that the proposed research agenda focuses on three problematics, relating to immediacy, investment, and ideology . As such, the text proposes to study the making of alternative futures by situating imaginaries of humanity becoming a multiplanetary species in the present realities of political economy.